The Impact of Purchase Restrictions Policy on Real Estate Market: Evidence from China - LIU, Yang (Advances in Social Sciences Research Journal, 2016)
Using city level monthly data from January 2009 to October 2012, this paper investigates the impact of purchase restrictions policy on real estate market in China. By difference-in-difference approach, we find that this restriction policy suppresses both the trading price and quantity in the short run; however, in the long run the price rebounds while quantity doesn't. Potential explanations of this difference between short-term and long-term effect lay in the decrease in supply and those newly issued policies which may induce a counter effect. Our paper contributes to a better evaluation of the current purchase restrictions policy from the perspective of both short and long run. Our findings may give policy makers some directions for further policy implementation.